2012
DOI: 10.1186/1754-6834-5-64
|View full text |Cite
|
Sign up to set email alerts
|

One-pot bioethanol production from cellulose by co-culture of Acremonium cellulolyticus and Saccharomyces cerevisiae

Abstract: BackgroundWhile the ethanol production from biomass by consolidated bioprocess (CBP) is considered to be the most ideal process, simultaneous saccharification and fermentation (SSF) is the most appropriate strategy in practice. In this study, one-pot bioethanol production, including cellulase production, saccharification of cellulose, and ethanol production, was investigated for the conversion of biomass to biofuel by co-culture of two different microorganisms such as a hyper cellulase producer, Acremonium cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 26 publications
2
33
0
2
Order By: Relevance
“…However the biological conversion of lignocellulose is still a much slower process than the enzymatic hydrolysis, especially the biological pretreatment of biomass is rate limiting [188]. For CBP, challenges also arise when aerobic microbes (ascomycetes) are used for cellulase production in combination with anaerobic fermentation by S. cerevisiae for bioethanol [189]. An onsite enzyme production applying a waste stream from a biorefinery setup as substrate might be just as economical and efficient as a CBP setup, especially with the many SSF bioreactor designs that enable the application of waste streams.…”
Section: Resultsmentioning
confidence: 99%
“…However the biological conversion of lignocellulose is still a much slower process than the enzymatic hydrolysis, especially the biological pretreatment of biomass is rate limiting [188]. For CBP, challenges also arise when aerobic microbes (ascomycetes) are used for cellulase production in combination with anaerobic fermentation by S. cerevisiae for bioethanol [189]. An onsite enzyme production applying a waste stream from a biorefinery setup as substrate might be just as economical and efficient as a CBP setup, especially with the many SSF bioreactor designs that enable the application of waste streams.…”
Section: Resultsmentioning
confidence: 99%
“…6 It was also reported that ethanol could be fermented from SolkaFloc (powdered cellulose) by using a co-culture in a one-pot process scheme. 7 A recent report used a mixture of acid-pretreated (i.e., HCl) and base-pretreated (NaOH) rice straw for ethanol production, but the pretreatment had to be conducted in different reactors. 8 Until now, the production of biofuels from lignocellulose using a one-pot conversion technology that includes pretreatment, saccharification, and fermentation has not been reported because of the significant technical challenges present.…”
Section: Introductionmentioning
confidence: 99%
“…Their results confirmed that all three Bacillus/yeast co-culture systems could achieve the cellulose saccharification and ethanol conversion simultaneously better than KR5 alone, and therefore, this microbial consortium could be of great potentials for integrating into a CBP system (Ho et al, 2012). Park et al (2012) developed co-culture system for one-pot bioethanol production, in which Acidothermus cellulolyticus C-1 and S. cerevisiae were co-cultured in a single reactor. After production of cellulase by A. cellulolyticus C-1, subsequently, S. cerevisiae was added to produce ethanol.…”
Section: Synthetic Microbial Consortium For Consolidated Production Omentioning
confidence: 52%